Mortality And Morbidity Pattern In Youth - Pandit Daksha D; S.G Jai; Pai N.P (Wolters Kluwer Medknow Publications, 1986)
Youths from an important segment in any society. The youth population has a significant role to play in the development of the Country as they are nationâ€s strength, hopes and future. Thus, it is pertinent to study the health situation of youth in India. Data regarding morbidity are not available. Data on morbidity condition of the youth population, if made available will help to design the preventive measures. A retrospective study was carried out by studying 2884 cases in the age group of 15 to 24 years from the records of B.Y.L Nair Charitable Hospital, Bombay. Out of 55.83% females in the study group, 51.24% of cases were due to pregnancy and related disorders. Out of the total cases admitted during the study period 23.06% were between 15 to 24 years of age group. Mortality rate was 2.08%. Other causes of morbidity were accidents (12.44%), gastrointestinal disorders (7.80%), respiratory disorders (5.96%) and psychological disorders (5.38%).